AN IMPLICIT FINITE DIFFERENCE METHOD FOR A FORCED KDV EQUATION - Wiryanto, L.H; A, Achirul (MATEMATIKA, 2008)
A finite difference method is developed to solve a forced KdV equation representing a surface elevation of fluid flowing on a channel with a small bump at the bottom. We indicate some difficulties in solving the equation since it has a nonlinear and third derivative terms. We present the technique in this paper to solve the equation. As the result, the numerical scheme gives solutions performing nonlinear wave-trains of water surface generated by the forcing term. Â